1991
DOI: 10.1159/000235524
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Induced Contraction of Human Isolated Lung Preparations Passively Sensitized with Monoclonal IgE: Effects of Indomethacin

Abstract: Human isolated lung preparations were passively sensitized using mouse monoclonal dinitrophenyl (DNP)-specific IgE antibodies. The contractile response to antigen (DNP-bovine serum albumin; DNP-BSA) was approximately 80% of the histamine response (50 µM: 0.20 ± 0.03 g/mm2) in bronchial muscle preparations. In passively sensitized pulmonary vascular and parenchymal preparations, the contraction to antigen was negligible. Indomethacin (1.7 µM; 30 min) did not alter the contractile response to DNP-BSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Prostacyclin in human pulmonary vessels 793 Norel et al, 1991). These data together may explain why Walch et al (1999) reported PGE 2 -induced relaxations in human pulmonary veins whereas arteries do not relax.…”
Section: Norel Et Almentioning
confidence: 96%
“…Prostacyclin in human pulmonary vessels 793 Norel et al, 1991). These data together may explain why Walch et al (1999) reported PGE 2 -induced relaxations in human pulmonary veins whereas arteries do not relax.…”
Section: Norel Et Almentioning
confidence: 96%
“…In endothelium, PGIS is by far the most abundant PG terminal synthase, with its expression level 5–100-fold higher than the other PG terminal synthases [54, 64, 65, 84]. Accordingly, PGI 2 is the most abundant endothelial eicosanoid, with expression levels 10–100-fold higher than that of the other eicosanoids in humans [107, 108] and in animals [54, 97, 109, 110]. …”
Section: Pgi2mentioning
confidence: 99%
“…PGI 2 triggers potent vasodilation [51, 57] by interacting with the PGI 2 receptor (IP) (Figure 1), which located in smooth muscle cells [108, 111]. The vasodilation effect of PGI 2 has also been shown in pig coronary arteries at low concentrations [58].…”
Section: Pgi2mentioning
confidence: 99%
“…22 However, the increase in contraction observed upon antigen challenge of human airways in vitro was small (approximately 30%) and in other protocols not observed. [1][2][3][4][5][6][7][8][9][10][11][12][13] This slight modulation in human airways is markedly different from that which was reported for guinea-pig tracheal preparations 23 where potentiation of antigen response was considerable (2to 3-fold) subsequent to the Ind treatment. Undem et al 4 have suggested that in human bronchial muscle preparations prostaglandin E,.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, other authors have shown inhibitory, or no effects, of Ind on antigenic challenge in human airways. [1][2][3][4][5][6][7][8][9][10][11][12][13] Recently, Bj/Srck and DahMn 14 have reported that potent LT antagonists and/or 5-1ipoxygenase inhibitors decreased the anti-IgE induced contractions. In other studies, such inhibition could be seen only in presence of additional inhibitors or antagonists.…”
Section: Introductionmentioning
confidence: 99%